2018
DOI: 10.1007/s40258-018-0426-2
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact Analysis of a Renal Point-of-Care Test in Dutch Community Pharmacies to Prevent Antibiotic-Related Hospitalizations

Abstract: Obtaining and evaluating renal function in community pharmacies by point of care tests is expected to be cost-saving in the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Of these 635 medications, 50 (7.9%) were affected by kidney function. Dose adjustment was recommended in 31 and discontinuation in 19. The primary care doctor accepted the recommendations for 14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 635 medications, 50 (7.9%) were affected by kidney function. Dose adjustment was recommended in 31 and discontinuation in 19. The primary care doctor accepted the recommendations for 14…”
Section: Resultsmentioning
confidence: 99%
“…Among them are services related to CKD, including screening and detection of asymptomatic patients [ 16 ], advice and reconciliation of medication in patients at hospital discharge [ 17 ], subsequent follow-up to detect medication related complications, including non-compliance [ 18 ]. In addition, a 2019 study used POCT measurement of kidney function (GFR) in community pharmacies in the Netherlands to prevent hospitalizations related to antibiotic adverse events [ 19 ]. In this study, the authors showed an annual saving of €86 per patient thanks to the possibility of measuring kidney function in Dutch community pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…LAB and POCT populations had a homogeneous distribution regarding age, creatinine, and glomerular filtration, essential data for establishing basal renal function. 10,13,17 Taking this into account, we considered that differences found during the study were not due to basal variation among LAB and POCT patients. There was only heterogeneity in sex distribution, which might affect some of the differences obtained.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]7,8,11,12 Publications available about POCT methods aimed at nephrologic patients are mostly for diagnosis and do not include BGA. [13][14][15][16] To the best of our knowledge, the present study assesses clinical, operative, and economic outcomes of POCT BGA in a nephrology department for the first time.…”
mentioning
confidence: 99%
“…This includes a role for simple-to-use, point-of-care (POC) creatinine methods, which potentially can be used for creatinine self-monitoring similar to self-monitoring blood glucose or blood ketone devices. The use of a POC whole blood creatinine monitoring system (BCMS) has been shown to be feasible and cost-effective in primary care settings and pharmacies, providing improvements to clinical services and cost savings in patient care [ 15 , 16 , 17 ]. However, a crucial issue in both evaluating and using a BCMS in CKD prevalence studies is the level of standardization of the test and reference methodology.…”
Section: Introductionmentioning
confidence: 99%